To eliminate the x terms and solve for y in the fewest steps, by which constants should the equations be multiplied by before adding the equations together? first equation: second equation:

Respuesta :

Answer:

See below.

Step-by-step explanation:

Here is an example:-

Solve by elimination:

2x - 3y  =   0

3x + 2y =  13

To eliminate the y terms Multiply the first equation by 2 and the second by 3. This gives:

4x  - 6y = 0

9x + 6y = 39      Adding the 2 equations:

13x + 0 = 39

13x = 39

x = 39/13 = 3

Finally we find y by plugging x = 3 into the first equation:

2(3) - 3y = 0

3y = 2(3) = 6

y = 2.

ACCESS MORE